IMPLEMENTATION GEOGRAPHIC INFORMATION SYSTEMS IN UMKM MAPPING IN THE BATU BATU REGENCY - Chika Nadia; Hambali Hambali; Hommy Dorthy Ellyany Sinaga (Jurnal Teknik Informatika (Jutif), 2022)
Searching for location points for UMKM activities in Batu Bara Regency, especially in the Cooperatives Service for Small and Medium Enterprises in Batu Bara Regency, is currently still using the manual method so that monitoring and evaluation is still not effective. This study aims was to implement a geographic information system for mapping the location of UMKM and displaying UMKM activities that provide convenience for the Office of Small and Medium Enterprises Cooperatives. This study used a method was carried out by determining the coordinates, namely latitude and longitude. The results of this study were a web-based geographic information system for finding the location of UMKM and their activities in the Batu Bara Regency area. This study concluded that the geographic information system that was built can help the Cooperatives Service for Small and Medium Enterprises in Batu Bara Regency in conducting searches for the location of UMKM activities and facilitating the monitoring and evaluation of UMKM activities.